Tratamento multidisciplinar do sorriso gengival - Kroll, Paulo Augusto [UNESP] (2010)
This work shows the treatment of gummy smile of a fifteen year old female patient, with severe incisal attrition for her age, resulting from bruxism and malocclusion. Due to the complexity of the case, there was a need to engage her in a team of three specialties, namely: orthodontics, periodontics and dentistry. The treatment lasted nearly three years to overcome the needs imposed by the case, which was satisfactorily solved